Susceptibility to Coolness at the Young Microspore Stage under High Nitrogen Supply in Rice (Oryza Sativa L.). Proteome Analysis of Mature Anthers - Takami Hayashi; Tomoya Yamaguchi; Katsuhiro Nakayama; Setsuko Komatsu; Setsuo Koike (Plant Production Science, 2006)
In vitro pollen germination experiment using agar plates showed that the growth under high nitrogen conditions enhanced the damage to pollen germination ability caused by the cooling at the young microspore stage. To clarify the physiological factors related to this damage to pollen germination, we performed the comparative proteome analysis of mature anthers and identified proteins that were changed by high nitrogen conditions or high nitrogen plus cooling conditions. Proteins were extracted from mature anther samples and separated by two-dimensional polyacrylamide gel electrophoresis. By comparing anther protein maps of the samples collected from the plants grown under standard nitrogen conditions, high nitrogen conditions and high nitrogen plus cooling conditions, we found 11 protein spots, which varied with the treatment. These protein spots were identified based on the rice proteome database and/or peptide mass fingerprinting (PMF) analysis after digestion with trypsin. Digested samples were analyzed by matrix-assisted laser desorption/ionization-time flight mass spectrometry to produce PMF data. Database searches using these PMF data revealed the identities of 9 proteins. Seven of these proteins were polypeptides involved in cell elongation, stress responses and sugar metabolism. The relation between the fluctuations of these proteins and the decrease in pollen germination are discussed.